Rap e religião: análise do imaginário religioso em Racionais Mc’s - ROCHA, Bruno de Carvalho (2022)
This research aims to identify and analyze the construction of the religious imaginary in the work of the São Paulo rap group Racionais Mc’s. Through the relationship between languages of religion, theories of the imaginary as well as cultural studies, the objective is to understand which are the symbols, myths and religious images mobilized in the album Sobrevivendo no inferno. In order to understand the characteristics that shape the religious imaginary of the work in question, 1) the historical, political and cultural aspects of religions in Brazil will be investigated, more specifically in the periphery of São Paulo, and to understand the reception of the Bible in the imaginary of the popular and peripheral culture through rap songs; 2) we will analyze the ways in which religion presents itself in the history of national rap, its mythical-poetic ways, and also its presence in the works and in the trajectory of the four members of Racionais Mc's; and finally, 3) through the historical context of both the album and the repercussions of its release as a book, some elements will be identified that make up the religious imagery of the album Sobrevivendo no inferno, its possible meanings and meanings as an “Another History of Salvation” , and the unfolding of a marginal reading of religion from Psalm 23. In the course of our study, we will use the concepts about the imaginary developed by Michel Maffesoli, but mainly, the method of Gilbert Durand from the anthropological structures of the imaginary, manifested by the image regimes (day and night). The path taken will offer an overview of the relationship between Brazilian rap and religion, but above all, it will help us to understand what we call “the religious imaginary in Racionais Mc’s”, through Sobrevivendo no inferno. In other words, his incessant invitation to survival, to the mythical-poetic imagination and to the possibilities of reinventing life that emerged in the dynamic movement of peripheral crossroads. We hope with this discussion from the Racionais Mc's, to contribute not only within the field of Sciences of religion, but also to inspire new discussions for the studies of rap and hip-hop(AU)